2010
DOI: 10.1124/mol.110.064196
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Striatal Cannabinoid CB1 Receptor Function Correlates with the Antianxiety Effects of Fatty Acid Amide Hydrolase Inhibition

Abstract: The endocannabinoid anandamide (AEA) plays a crucial role in emotional control, and inhibition of its degradation by the fatty acid amide hydrolase (FAAH) has a potent antianxiety effect. The mechanism by which the magnification of AEA activity reduces anxiety is still largely undetermined. By using FAAH mutant mice and both intraperitoneal and intracerebroventricular administration of the FAAH inhibitor (3Ј-(aminocarbonyl)[1,1Ј-biphenyl]-3-yl)-cyclohexylcarbamate (URB597), we found that enhanced AEA signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
45
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 56 publications
(91 reference statements)
8
45
0
Order By: Relevance
“…Consistent with this model, we have demonstrated that stress-induced release of CRH rapidly triggers FAAH activity in the BLA to reduce AEA signaling, which in turn promotes the generation of anxiety (Gray et al, 2015). Importantly, central AEA levels are negatively correlated with anxiety-like behaviors , and elevating AEA signaling can effectively curb anxiety induced by both acute and chronic stress Campos et al, 2010;Hill et al, 2013b;Lomazzo et al, 2015;Rossi et al, 2010). As such, it has been proposed that AEA may function as a mediator of 'emotional homeostasis' (Haller et al, 2013;Marco and Viveros, 2009), functioning to keep anxiety at bay in resting conditions, from which disruption of this signal by stress could contribute to the generation of an anxious state (Gunduz-Cinar et al, 2013a).…”
Section: Functional Role Of Ecb Signaling In the Neurobiological Effesupporting
confidence: 69%
See 1 more Smart Citation
“…Consistent with this model, we have demonstrated that stress-induced release of CRH rapidly triggers FAAH activity in the BLA to reduce AEA signaling, which in turn promotes the generation of anxiety (Gray et al, 2015). Importantly, central AEA levels are negatively correlated with anxiety-like behaviors , and elevating AEA signaling can effectively curb anxiety induced by both acute and chronic stress Campos et al, 2010;Hill et al, 2013b;Lomazzo et al, 2015;Rossi et al, 2010). As such, it has been proposed that AEA may function as a mediator of 'emotional homeostasis' (Haller et al, 2013;Marco and Viveros, 2009), functioning to keep anxiety at bay in resting conditions, from which disruption of this signal by stress could contribute to the generation of an anxious state (Gunduz-Cinar et al, 2013a).…”
Section: Functional Role Of Ecb Signaling In the Neurobiological Effesupporting
confidence: 69%
“…With the exception of the PFC, chronic stress is associated with a downregulation of CB1 receptor expression. Using electrophysiology, mRNA, protein, and radioligand binding, downregulation of the CB1 receptor has been found in the hippocampus (Hill et al, 2005b(Hill et al, , 2008bHu et al, 2011;Lee and Hill, 2013;Reich et al, 2009), hypothalamus (Hill et al, 2008b;Wamsteeker Cusulin et al, 2014;Wamsteeker et al, 2010), striatum (Hill et al, 2008b;Rossi et al, 2008Rossi et al, , 2010Wang et al, 2010), and dorsal root ganglion (Hong et al, 2011) following exposure to an array of both chronic homotypic and heterotypic stressors. The amygdala appears to be somewhat resistant to these effects as many reports have demonstrated no effect of chronic stress on CB1 expression using radioligand binding (Hill et al, 2008b;Lee and Hill, 2013); at the electrophysiological level, however, chronic homotypic stress has been shown to desensitize CB1 receptors in the BLA, at least on GABAergic terminals (Patel et al, 2009).…”
Section: Effects Of Acute and Chronic Stress On Cb1 Receptorsmentioning
confidence: 99%
“…The ECS has important roles in both psychiatric disorders (Lutz, 2009;Hill and Patel, 2013) and pain states (Kinsey et al, 2009Piomelli et al, 2006;Piomelli and Sasso, 2014). The anxiolytic and analgesic properties of inhibitors of FAAH and MAGL have been extensively described (Kathuria et al, 2003;Jhaveri et al, 2006;Rossi et al, 2010;Sciolino et al, 2011;Ghosh et al, 2013;Kinsey et al, 2013). Therefore, targeting the ECS may represent a therapeutic strategy, particularly for the treatment of chronic pain associated with emotional imbalance.…”
Section: Discussionmentioning
confidence: 99%
“…2-AG acts preferentially on CB 1 receptors in GABAergic neurons; in fact, the simulation of its synthesis was found to reduce GABAergic, but not glutamatergic neurotransmission [139,140]. Conversely, anandamide may inhibit the release of glutamate by activating CB 1 receptors in glutamatergic neurons [141].…”
Section: A Brief Outline On the Endocannabinoid Systemmentioning
confidence: 98%